Taohong Siwu Decoction alleviates high salt-induced calcium overload and ferroptosis in vascular endothelial cells in hypertension by regulating ATF4 - Lam, Lai Kwan; Xu, Peng-Li; Xie, Peng-Cheng; Liang, Qiu-er; Xie, Ting; Poon, Lee Yam; Xiao, Ya; Chen, Li-Guo (Frontiers in Nutrition, 2025)
BackgroundTaohong Siwu Decoction (THSWD), a traditional Chinese medicine formula, is increasingly applied in clinical practice for hypertension management. Our previous research demonstrated that THSWD alleviates high-salt-induced hypertension in mice. This study aims to further elucidate the underlying mechanisms of THSWD in treating hypertension.MethodsThe chemical composition of THSWD was identified using UPLC-Q/TOF-MS in earlier research. In this study, we performed both in vivo and in vitro experiments. ATF4+/− mice (KO) and C57BL/6 mice (WT) were fed a high-salt diet with or without THSWD treatment. Human aortic endothelial cells (HAECs) were cultured in high-NaCl conditions, with or without ATF4 inhibition. Blood pressure, vascular injury, calcium overload, and ferroptosis were measured to evaluate the protective effects of THSWD.ResultsIn vivo, a high-salt diet caused hypertension, vascular wall thickening, vascular injury, calcium overload, and ferroptosis, all of which were significantly alleviated by THSWD and the calcium-channel blocker nifedipine (NI). THSWD also reduced the high-salt-induced overexpression of ATF4. Similar effects were observed in vitro, where THSWD, the ferroptosis inhibitor ferrostatin-1 (Fer-1), the intracellular calcium chelator BAPTA-AM, and NI improved calcium overload and ferroptosis caused by high-NaCl. This was accompanied by reduced expression of CaMK4, CACNA1C, IP3R, RyR2, GPX4, ACSL4, and LPCAT3. Furthermore, compared to ATF4+/− mice on a high-salt diet, those treated with THSWD showed greater reductions in blood pressure, improved vascular endothelial function, and better suppression of calcium overload and ferroptosis. Inhibition of ATF4 or co-treatment with siATF4 and THSWD in vitro also restored abnormal biomarker levels (iron, calcium, 12-HETE, 15-HETE, GSH, GSH/GSSG, MDA, and LPO) and normalized calcium overload- and ferroptosis-related markers.ConclusionTHSWD effectively lowers blood pressure and protects against vascular damage in high-salt-induced hypertension. Its protective effects are achieved by inhibiting calcium overload and ferroptosis through the regulation of ATF4.